Biomimetic spinning of artificial spider silk from a chimeric minispidroin. - Andersson, M; Jia, Q; Abella, A; Lee, X; Landreh, M; Purhonen, P; Hebert, H; Tenje, M; Robinson, C; Meng, Q; Plaza, G; Johansson, J; et al. (Nature Publishing Group, 2017)
Herein we present a chimeric recombinant spider silk protein (spidroin) whose aqueous solubility equals that of native spider silk dope and a spinning device that is based solely on aqueous buffers, shear forces and lowered pH. The process recapitulates the complex molecular mechanisms that dictate native spider silk spinning and is highly efficient; spidroin from one liter of bacterial shake-flask culture is enough to spin a kilometer of the hitherto toughest as-spun artificial spider silk fiber.